ANALISIS PRODUKTIVITAS PADI DENGAN MENGGUNAKAN BENIH SERTIFIKAT DAN BENIH NON SERTIFIKAT DI KECAMATAN BANYUBIRU KABUPATEN SEMARANG - Rizky Andini (Economics Development Analysis Journal, 2012)
The purpose from this research indicated diferrence of real productivity rice and diferrence of income effort of rice that using sertificate seed and non sertificate in Banyubiru. Population in this research is the farmers of rice in Banyubiru a number of 2080 farmer is used sertificate seed and 2324 farmer is used seed non sertificate. This Sample of research was taken Propotional Stratiefied Random sampling and is derived 48 respondent that used sertificate seed and 52 respondent used seed non sertificate. Variable of this research is produtivity of rice and using sertificate seed and non sertificate. Data analysis method used statistic test with Software SPSS16.0 and profit analysis Return/Cost radio(R/C). Productivity of rice that used seed non sertificate 0,88 kg/ha. Value of ratio R/C for effort of rice that used seed non sertificate 4,41 and R/C for effort of rice used seed serticate 2,51. Using sertificate seed is not more better from seed non sertificate and seed non sertificate is more profit.